2018
DOI: 10.6026/97320630014236
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of anti-angiogenic effects of noscapine derivatives

Abstract: Angiogenesis, the formation of new capillaries from pre-existing vessels, is essential for tumor progression. Synthetic derivatives of anti-cancer compound, noscapine (an opium alkaloid) such as Cl-noscapine, Br-noscapine and Folate-noscapine along with two of the reference compounds, TNP-470 and paclitaxel were examined for anti-angiogenic activities by using human umbilical vein endothelial cells (HUVECs). The noscapine derivatives showed anti-angiogenic activity albeit at high concentration compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Studies have shown that all noscapine derivatives showed dose-dependent antiangiogenic activity after 72 hours of treatment than those that did not receive noscapine [ 116 ]. According to the National Cancer Institute (NCI), IC 50 > 20, 6.9 µ M for Br-noscapine, and 6.79 µ M for folate-noscapine can inhibit VEGF ( Table 2 ) [ 117 ].…”
Section: Targets Of Noscapine Receptors and Signalling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that all noscapine derivatives showed dose-dependent antiangiogenic activity after 72 hours of treatment than those that did not receive noscapine [ 116 ]. According to the National Cancer Institute (NCI), IC 50 > 20, 6.9 µ M for Br-noscapine, and 6.79 µ M for folate-noscapine can inhibit VEGF ( Table 2 ) [ 117 ].…”
Section: Targets Of Noscapine Receptors and Signalling Pathwaysmentioning
confidence: 99%
“…Thus, noscapine has anti-inflammatory, antiangiogenesis, and antimetastatic effects. In addition, examination of hypoxia conditions in human glioma cells has shown that noscapine has an inhibitory effect on VEGF, inhibits angiogenesis, and inhibits TNF- α and NF- κ B [ 116 ].…”
Section: Targets Of Noscapine Receptors and Signalling Pathwaysmentioning
confidence: 99%
“…Understanding how the, necessarily exquisite, acceptor specificity is achieved will be central to both enzyme and system-wide engineering campaigns to understand, modify, and exploit plant secondary metabolism. As noscapine-derived and inspired compounds become increasingly important as therapeutic agents (for recent examples, see refs and ) and in light of breakthroughs in the biosynthesis of noscapine in heterologous hosts systems, we believe the dissection of PSMT1 reported here is an important step toward the goal of being able to predict substrate specificity of the growing number of methyltransferase genes in the public domain that will ultimately contribute to their exploitation in rational engineering of natural products.…”
Section: Resultsmentioning
confidence: 99%
“…For example, nosine and it analogs have been shown to have no sign of neurotoxicity or immunosuppression in ovarian cancer studies research. On the other hand, noscapine has been demonstrated to have neuroprotective effects in neurodegenerative disease and stroke mouse models ( 62 ). Concerning its anti-tumor effect on human prostate cancer cell lines LNCaP and PC-3, it was found that the joint application of paclitaxel and nicardipine can increase the percentage of apoptotic cells.…”
Section: Colchicine Binding Domainmentioning
confidence: 99%